THE EFFECTS OF IMPACT MODIFIERS ON THE PROCESSABILITY AND THE TOUGHNESS OF POLY VINYL CHLORIDE PROFILES - Nutt Lumpikanond; Sirijutaratana Covavisaruch (Center for Science & Technology of Advanced Materials - National Nuclear Energy Agency, 2011)
THE EFFECTS OF IMPACT MODIFIERS ON THE PROCESSABILITY AND THE TOUGHNESS OF POLY VINYL CHLORIDE PROFILES. Extruded Poly Vinyl Chloride (PVC) door profile and window profiles often fail at the bend. This research aims to reduce such problem by enhancing the toughness of the PVC profiles while still maintaining their load bearing function and stiffness. Three impact modifiers namely methacrylate-butadiene-styrene (MBS), chlorinated polyethylene (CPE) and nano-scaled nitrile butadiene rubber (NBR) were employed in the PVC profiles at 1-11 phr. The processability assessed by rheometric study revealed only a slight increase in the torque required to process the melt PVC dosed with CPE and nano NBR while that required for the PVC with MBS was raised quite significantly. Although the PVC modified with MBS melted faster at a lower temperature, a rapid rise of temperature was observed during processing. The heat was probably due to the higher friction and shear induced by the rather viscous PVC melt dosed with MBS. Mechanical tests in terms of impact energy, stiffness and hardness revealed that the toughening efficiency of all three impact modifiers were close at low content, but at around 9 and 11 phr, the MBS and the CPE enhanced the impact energy quite rapidly by four folds while their corresponding hardness and stiffness were lowered considerably.